2020
DOI: 10.2147/ott.s234758
|View full text |Cite
|
Sign up to set email alerts
|

<p>Elevation in the Expression of circ_0079586 Predicts Poor Prognosis and Accelerates Progression in Glioma via Interactions with the miR-183-5p/<em>MDM4</em> Signaling Pathway</p>

Abstract: Purpose: Glioma (GM) usually presents with an aggressive behavior and has a poor survival outcome. The abnormal expression of circular RNAs (circRNAs) has already been detected in GM, and circ_0079586 was found to have an increased expression in GM tumors. Patients and Methods: We assessed the differences in the expression of circ_0079586 in GM tissues (N=60) and cell lines (N=5) using qRT-PCR. The clinical value of circ_0079586 was measured by Fisher's exact test and Kaplan-Meier and Cox regression analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For example, [ 29 ] circTADA2As hinders the progression and metastasis of BC by targeting miR-203a-3p/SOCS3 axis. Other studies found that the enhanced circ_0079586 can predict the poor prognosis of glioma and accelerate its progression through the interaction with miR-183-5p/MDM4 [ 30 ]. In order to verify that circ_RPPH1 has the effect as ceRNA, we first localized it.…”
Section: Discussionmentioning
confidence: 99%
“…For example, [ 29 ] circTADA2As hinders the progression and metastasis of BC by targeting miR-203a-3p/SOCS3 axis. Other studies found that the enhanced circ_0079586 can predict the poor prognosis of glioma and accelerate its progression through the interaction with miR-183-5p/MDM4 [ 30 ]. In order to verify that circ_RPPH1 has the effect as ceRNA, we first localized it.…”
Section: Discussionmentioning
confidence: 99%
“…Several circRNAs have been reported to be dysregulated in human endothelial cells 27 , 28 . Specially, circRNA_0079586 was found to accelerate the progression of glioma via interacting with miR-183-5p, while circRNA_RanGAP1 was found to facilitate gastric cancer invasion and metastasis via interacting with miR-877-3p 29 , 30 . Moreover, previous reports demonstrated that MPO not only contributed to the formation and rupture of cerebral aneurysm, but was also correlated with the degenerative remodeling predisposition to saccular intracranial aneurysm wall rupture 22 , 31 .…”
Section: Introductionmentioning
confidence: 99%